Pengaruh Sistem Manajemen Informasi Terintegrasi dan Teknologi Internet Of Things Terhadap Efisiensi Manajemen Persediaan di Ramayana Ciputat - Alfarabi, Farhan; Hananto, Djoko (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of implementing Integrated Information Management Systems (SMIT) and Internet of Things (IoT) technology on inventory management efficiency at Ramayana Ciputat. The background of this research stems from the increasing complexity of inventory management in the retail sector in the digital era. Inventory efficiency is crucial to reducing operational costs and enhancing competitiveness. This research uses a quantitative approach by distributing questionnaires to 20 operational staff members. Data were analyzed using multiple linear regression with SPSS software. The results show that both SMIT and IoT have a significant positive effect—individually and simultaneously—on inventory management efficiency. These findings highlight the importance of digitalizing information systems and utilizing sensor technology to optimize retail stock management.